TRUST CENTRIC FRAMEWORK FOR ARTIFICIAL INTELLIGENCE INTEGRATION IN PUBLIC ADMINISTRATION - Shaza Khalid (Universitas Budi Luhur, 2026)
Abstract: Artificial Intelligence (AI) and digital transformation are changing the global public governance landscape in today's fast-changing world. This paper addresses the important nexus of technological progress and institutional trust in the context of the Presidential Decree, which has been proclaimed as the Year of Digitalization and Artificial Intelligence. While AI can introduce an unprecedented level of efficiency and data-driven decision-making in public administration, it is also associated with the